2020
DOI: 10.1115/1.4045972
|View full text |Cite
|
Sign up to set email alerts
|

A Translational Three-Degrees-of-Freedom Parallel Mechanism With Partial Motion Decoupling and Analytic Direct Kinematics

Abstract: According to the topological design theory and method of parallel mechanism (PM) based on position and orientation characteristic (POC) equations, this paper studied a 3-DOF translational PM that has three advantages, i.e., (i) it consists of three fixed actuated prismatic joints, (ii) the PM has analytic solutions to the direct and inverse kinematic problems, and (iii) the PM is of partial motion decoupling property. Firstly, the main topological characteristics, such as the POC, degree of freedom and couplin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…It is known from Section ‘Analysis of coupling degree’ that the mechanism is composed of two SKC 1 and SKC 2 with zero constraint degree. With the method to solve the forward position problem 41 based on the topological characteristics, 42 displacement analysis is carried out along with the two independent SKCs.…”
Section: Kinematic Analysis Of Vari-orthoglide Pmmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known from Section ‘Analysis of coupling degree’ that the mechanism is composed of two SKC 1 and SKC 2 with zero constraint degree. With the method to solve the forward position problem 41 based on the topological characteristics, 42 displacement analysis is carried out along with the two independent SKCs.…”
Section: Kinematic Analysis Of Vari-orthoglide Pmmentioning
confidence: 99%
“…By means of the Gröbner-based elimination method, 41,45 the serial and parallel singular loci of SKC 2 can be identified with Maple™, which are displayed in Figure 15. It can be observed that the serial singularity loci forms a closed volume in the shape of cylinder, and the parallel singularity loci are located inside.…”
Section: Workpace Analysis Based On Skcsmentioning
confidence: 99%
“…According to the kinematic modeling principle and method based on topological characteristics [6], [9] proposed by the author, the symbolic FPS of this PM can be performed below.…”
Section: Solving Symbolic Forward Positionmentioning
confidence: 99%
“…To understand the kinematic performance of a linkage, many scholars have been proposing different theories (McCarthy, 1990;Duffy, 1996;Davidson and Hunt, 2004;Dai, 2014;Zhao et al, 2016;Amiri and Mazaheri, 2020;Faghidian and Mohammad-Sedighi, 2020), methods (Angeles, 1982;Kong et al, 2018;Yang et al, 2018;Kong et al, 2019;Shen et al, 2020), algorithms (García de Jalón and Bayo, 1994;Kong et al, 2016;Saura et al, 2019) and software (Brát and Lederer, 1973;García de Jalón and Bayo, 1994;Wu et al, 2009;Wu et al, 2017). This paper focuses on an algorithm in the screw coordinates to solve the velocity of articulated planar linkage and investigates the displacement and acceleration.…”
Section: Introductionmentioning
confidence: 99%